The Real Practice Prescribing Antibiotics in Outpatients: A Failed Control Case Assessed through the Simulated Patient Method - María Guadalupe Miranda-Novales; Karen Flores-Moreno; Mauricio Rodríguez-Álvarez; Yolanda López-Vidal; José Luis Soto-Hernández; Fortino Solórzano Santos; Samuel Ponce- (MDPI AG, 2023)
The first level of medical care provides the largest number of consultations for the most frequent diseases at the community level, including acute pharyngitis (AP), acute diarrhoea (AD) and uncomplicated acute urinary tract infections (UAUTIs). The inappropriate use of antibiotics in these diseases represents a high risk for the generation of antimicrobial resistance (AMR) in bacteria causing community infections. To evaluate the patterns of medical prescription for these diseases in medical offices adjacent to pharmacies, we used an adult simulated patient (SP) method representing the three diseases, AP, AD and UAUTI. Each person played a role in one of the three diseases, with the signs and symptoms described in the national clinical practice guidelines (CPGs). Diagnostic accuracy and therapeutic management were assessed. Information from 280 consultations in the Mexico City area was obtained. For the 101 AP consultations, in 90 cases (89.1%), one or more antibiotics or antivirals were prescribed; for the 127 AD, in 104 cases (81.8%), one or more antiparasitic drugs or intestinal antiseptics were prescribed; for the scenarios involving UAUTIs in adult women, in 51 of 52 cases (98.1%) one antibiotic was prescribed. The antibiotic group with the highest prescription pattern for AP, AD and UAUTIs was aminopenicillins and benzylpenicillins [27/90 (30%)], co-trimoxazole [35/104 (27.6%)] and quinolones [38/51 (73.1%)], respectively. Our findings reveal the highly inappropriate use of antibiotics for AP and AD in a sector of the first level of health care, which could be a widespread phenomenon at the regional and national level and highlights the urgent need to update antibiotic prescriptions for UAUTIs according to local resistance patterns. Supervision of adherence to the CPGs is needed, as well as raising awareness about the rational use of antibiotics and the threat posed by AMR at the first level of care.